2015
DOI: 10.2215/cjn.01000115
|View full text |Cite
|
Sign up to set email alerts
|

Living-Donor Kidney Transplantation

Abstract: Live-donor kidney transplantation (LDKT) is the best treatment for eligible people with late-stage kidney disease. Despite this, living kidney donation rates have declined in the United States in recent years. A potential source of this decline is the financial impact on potential and actual living kidney donors (LKDs). Recent evidence indicates that the economic climate may be associated with the decline in LDKT and that there are nontrivial financial ramifications for some LKDs. In June 2014, the American So… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
113
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(117 citation statements)
references
References 30 publications
2
113
0
Order By: Relevance
“…We found that some donors, whether labs are drawn in the transplant clinic or by a provider closer to home, incur costs associated with followup care-a likely unintended consequence of this shift in mandated follow-up data collection. We strongly support the recommendation from the 2014 Consensus Conference on Best Practices in Living Kidney Donation to develop a Living Kidney Donation Financial Toolkit, which would provide a summary of known financial risks, an equation model for estimating donation-related costs, linkages to NLDAC and other sources of financial assistance, and strategies for talking to employers about recovery time and access to benefits (10,29).…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…We found that some donors, whether labs are drawn in the transplant clinic or by a provider closer to home, incur costs associated with followup care-a likely unintended consequence of this shift in mandated follow-up data collection. We strongly support the recommendation from the 2014 Consensus Conference on Best Practices in Living Kidney Donation to develop a Living Kidney Donation Financial Toolkit, which would provide a summary of known financial risks, an equation model for estimating donation-related costs, linkages to NLDAC and other sources of financial assistance, and strategies for talking to employers about recovery time and access to benefits (10,29).…”
Section: Discussionmentioning
confidence: 71%
“…Collectively, LKDs received $118 654 in total financial assistance, against a backdrop of $622 324 in direct and indirect expenses. NLDAC provided the most financial support, both in percentage of donors helped (9%) and funds disbursed ($57 389); however, it is our impression that these financial assistance programs are fragmented, inaccessible to many donors, and limited in what types of expenses are reimbursable (1,10). NLDAC, for instance, considers the financial resources of both donors and their recipients in determining whether eligibility criteria are met, and legislation establishing the program specifically prohibits reimbursement of lost wages (1).…”
Section: Discussionmentioning
confidence: 99%
“…Particularly troubling is that lack of insurance is more common in LKDs with known health disparities (e.g., minorities, least educated) and those who have two or more pre-existing health risk factors (e.g., obesity, smoking, hypertension, low eGFR, proteinuria). Data from this study should be considered in discussions regarding the provision of health insurance benefits to previous and future LKDs in the U.S.[8,10,23,42,43]…”
Section: Discussionmentioning
confidence: 99%
“…[3–6] One characteristic that remains controversial in determining donation eligibility is the presence or absence of health insurance in the potential LKD. [4–10] In a survey of U.S. kidney transplant programs, the lack of health insurance in the donor was an absolute and relative contraindication to donation in 15% and 42% of programs, respectively. [4]…”
Section: Introductionmentioning
confidence: 99%
“…For many donors, unreimbursed wages lost during recovery are a substantial stressor. 5,6 Most donors also have outofpocket inci dental expenses (such as travel, child care and unreimbursed medical expenses) that are not insignificant. We commend states that have adopted policies to reimburse lost wages and reduce outofpocket costs for donors.…”
mentioning
confidence: 99%